Effects of narcotic analgesic drugs on human Oddi’s sphincter motility - Wu, Shuo-Dong (World J Gastroenterol, 2004)
AIM: To assess the effects of intramuscular analgesics (morphine, Ap-237, pethidine and tramadol) on human Oddi's sphincter motility with choledochoscope manometry. METHODS: A total of 70 patients having T tubes after cholecystectomy and choledochotomy were assessed by choledochoscope manometry. They were randomly divided into morphine group, Ap-237 group, pethidine group and tramadol group. Basal pressure of Oddi's sphincter (BPOS), amplitude of phasic contractions (SOCA), frequency of phasic contractions (SOF), duration of phasic contractions (SOD), duodenal pressure (DP) and common bile duct pressure (CBDP) were scored and analyzed. All narcotic analgesic drugs were administered intramuscularly. RESULTS: Levels of BPOS, SOCA and SOF were increased after injection of morphine and Ap-237 (P < 0.05), level of CBDP was increased from 4.97 ± 3.87 mmHg to 8.62 ± 7.43 mmHg (10 min later) and 7.32 ± 5.95 mmHg (20 min later) after injection of morphine (P < 0.01). No apparent change occurred after intramuscular injection of pethidine. Level of BPOS was increased from 7.01 ± 5.50 mmHg to 2.87 ± 2.78 mmHg 10 min after injection of tramadol and SOCA was decreased from 63.34 ± 35.29 mmHg to 45.90 ± 27.86 mmHg (10 min later, P < 0.05) and 35.97 ± 24.30 (20 min later, P < 0.01) after administration of tramadol. CONCLUSION: All these findings indicate that Oddi’s sphincter manometry via choledochoscope is a practical and new way to study the dynamics of Oddi’ s sphincter. The regular dose of morphine and Ap-237 could increase BPOS, SOF and SOCA. Morphine could increase the level of CBDP, demonstrating an excitatory effect on the sphincter of Oddi. Pethidine had no effect on Oddi's sphincter motility. Tramadol shows an inhibitory effect on the motility of the sphincter of Oddi and decreases levels of BPOS and SOCA.